Analisis Kemampuan Literasi Siswa di Sekolah Dasar pada Program Kampus Mengajar II di Kabupaten Sinjai - Amalia Putri, Indah; Supriadi, Supriadi; Erwin Nurdiansyah (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstract:This study aims to identify the barriers experienced by third-grade students at Public Elementary School 226 Saukangnge, Sinjai Regency, in developing reading literacy, as well as to examine the factors contributing to their reading difficulties. This research adopts a descriptive qualitative approach. The study was conducted at Public Elementary School 226 Saukangnge, located in Batu Belerang Village, Sinjai Borong Subdistrict, Sinjai Regency. The focus of the research includes reading literacy and the "Kampus Mengajar" (Teaching Campus) program. The instruments used in this study consisted of observation sheets, interview results, and documentation. The findings revealed that several students had difficulty recalling the complete alphabet, and some still lacked fluency in decoding words. Three students received focused assistance through reading activities. The implementation of classroom mentoring for students with low reading literacy had a significant impact on both their literacy skills and their personal development.